Host immunity and HBV S gene mutation in HBsAg-negative HBV-infected patients - Liu, Xin; Chen, Shu-xiang; Liu, Hui; Lou, Jin-li (Frontiers in Immunology, 2023)
Background Clinically, some patients whose HBsAg becomes negative owing to antiviral therapy or spontaneously still show a low level of HBV DNA persistence in serum. T-lymphocyte subsets, cytokine levels and HBV S gene sequences were analyzed in this study. Methods A total of 52 HBsAg-negative and HBV DNA-positive patients(HBsAg-/HBV DNA+ patients), 52 persistently HBsAg-positive patients(HBsAg+/HBV DNA+ patients) and 32 healthy people were evaluated. T-lymphocyte subsets of these patients were detected by flow cytometry, serum cytokines and chemokines were detected by the Luminex technique, and the HBV S region was evaluated by Sanger sequencing. T%, T-lymphocyte, CD8+ and CD4+T lymphocyte were lower in the HBsAg-negative group than in the HC group. Compared with the HBsAg-positive group, the HBsAg-negative group had lower levels in T lymphocyte %, CD8+T lymphocyte %, CD8+T lymphocyte and CD4/CD8. These difference were statistically significant (P<0.05). Serum IFN-γ, IFN-α and FLT-3L levels were significantly higher in the HBsAg-negative group than in the HBsAg-positive group (P<0.05). However, levels of many cytokines related to inflammation (i.e., IL-6, IL-8, IL10, IL-12, IL-17A) were lower in the HBsAg-negative group. Fifty-two HBsAg-negative samples were sequenced, revealing high-frequency amino acid substitution sites in the HBV S protein, including immune escape mutations (i.e.